Altered frequency of peripheral B‐cell subsets and their correlation with disease activity in patients with systemic lupus erythematosus: A comprehensive analysis. Issue 20 (12th September 2020) - Peng, Yanxia; Guo, Fengbiao; Liao, Shuzhen; Liao, Huanjin; Xiao, Haiyan; Yang, Lawei; Liu, Hua‐feng; Pan, Qingjun
Abstract: Alternations of peripheral B‐cell subsets are closely related to disease activity in systemic lupus erythematosus (SLE) and may also predict the relapse of SLE. In this study, we aimed to comprehensively analyse the frequency of peripheral B‐cell subsets, and their correlation with disease activity in patients with SLE. The results showed that for B‐cell subsets in the antigen‐independent differentiation stage, the frequency of the peripheral hematopoietic stem cell (HSC) subset in all patients with SLE was significantly higher than that of control patients. Surprisingly, several significant correlations were noted in newly diagnosed patients with SLE including a positive correlation in the frequency of the common lymphoid progenitor cell (CLP) with cholesterol serum levels. For B‐cell subsets in the antigen‐dependent differentiation stage, the frequency of naïve B‐cell (N‐B) subsets in all patients with SLE was significantly higher than that in the control patients. Moreover, the frequency of plasmablasts positively correlated with the SLEDAI score in the newly diagnosed patients. For memory B‐cell (M‐B) subtypes in the antigen‐dependent differentiation stage, the frequency of the class‐switched memory B‐cell (CSM‐B) subsets was positively correlated with the serum levels of complement C3. Notably, the frequency of the CSM‐B subset also negatively correlated with the SLEDAI score, whereas the non–class‐switched memory B‐cell (NSM‐B) subset was positively correlated with the serum levels of haemoglobin. Collectively, these findings may contribute to a better understanding of the role played by different B‐cell subsets in the pathogenesis of SLE.